Interaction and Mutual Activation of Different Innate Immune Cells Is Necessary to Kill and Clear Hepatitis C Virus-Infected Cells - Klöss, Volker; Grünvogel, Oliver; Wabnitz, Guido; Eigenbrod, Tatjana; Ehrhardt, Stefanie; Lasitschka, Felix; Lohmann, Volker; Dalpke, Alexander H. (Frontiers in Immunology, 2017)
Innate immune cells can sense hepatitis C virus (HCV)-infected cells and respond with anti-viral actions including secretion of interferons (IFNs). In previous studies, the response of individual innate immune cells against HCV was analyzed in detail. We hypothesized that interaction of multiple innate immune cells increases the magnitude of the immune response and eventually leads to clearance of HCV-infected cells. To investigate this, we co-cultured Huh-7 HCV subgenomic replicon (SGR) cells with peripheral blood mononuclear cells (PBMCs). We confirm secretion of IFNα by plasmacytoid dendritic cells (pDCs) and IFNγ by natural killer (NK) cells in the co-culture setup. Moreover, we observed that also monocytes contribute to the anti-viral response. Flow cytometry and ImageStream analysis demonstrated that monocytes take up material from HCV SGR cells in co-culture with PBMCs. Preceding the uptake, PBMCs caused apoptosis of HCV SGR cells by tumor necrosis factor-related apoptosis inducing ligand (TRAIL) expression on NK cells. We observed that only the interplay of monocytes, pDCs, and NK cells resulted in efficient clearance of HCV SGR cells, while these cell populations alone did not kill HCV SGR cells. Despite similar TRAIL receptor expression on Huh-7 control cells and HCV SGR cells, HCV activated PBMCs specifically killed HCV SGR cells and did not target Huh-7 control cells. Finally, we showed that HCV replicating cells per se are sensitive toward TRAIL-induced apoptosis. Our results highlight the importance of the interplay of different innate immune cells to initiate an efficient, rapid, and specific response against HCV-infected cells.